Sociocultural Study The Evolution Of Palang Pintu : Past Vs Present - Erlangga, Muhammad Rafli; Herlyna, Herlyna; Syamsuar, Fauzi (STIBA IEC JAKARTA, 2025)
Palang Pintu is a typical tradition of the Betawi people which contains cultural, artistic and philosophical values in the wedding procession. However, over time, several sessions in the Palang Pintu tradition have undergone changes. This research aims to identify changes that occur and analyze the factors that influence them.This research uses qualitative methods with a sociocultural study approach by Vygotsky. Data was collected through observation and interviews with cultural actors.. Analysis was carried out to compare Palang Pintu practices in the past and present in order to understand the shift in cultural values and meanings within them.The results of the research show that several elements in Palang Pintu have undergone modifications, such as reducing or adapting traditional pantun scenes, pencak silat, as well as the involvement of cultural figures. The main factors of this change include modernization, shifts in social values, and adaptation to current societal preferences.As an effort to preserve culture, this research recommends education regarding the importance of maintaining traditional elements in Palang Pintu, as well as encouragement for the younger generation to continue preserving cultural heritage by adapting it wisely without losing its original essence.